Job stress and depression among Malaysian anti-drug professionals: the moderating role of job-related coping strategies - Md Nordin, Noradilah; Dahamat Azam, Naqi; Rosnon, Mohd Roslan; Abu Talib, Mansor (Frontiers Research Foundation, 2022)
Depression can cause negative consequences to workers' health and social functioning, such as poor work productivity, mental disorders, and suicide. Existing studies have argued that job stress is closely related to depression in many professions. Yet, information on how coping strategies play a significant role in the relationships among Malaysian anti-drug professionals is still scarce. Thus, the aim of this study was to examine to what extent coping strategies moderate the relationship between job stress and depression among Malaysian anti-drug professionals. A total of 3,356 National Antidrug Agency (NADA) officers aged between 21 and 59 years completed online self-report measures of depression, job stress, and job-related control coping and avoidant coping behaviors. The results showed that job stress was strongly correlated with depression, and both coping strategies were found to significantly moderate the correlations. The correlations between stress and depression were stronger among participants who had higher levels of avoidant coping or those who had lower levels of control coping. To conclude, this study highlights the importance of considering job stress and coping behaviors to understand anti-drug professionals' mental health during this challenging COVID-19 pandemic.